PERANAN WORK LIFE BALANCE DALAM MENINGKATKAN PRODUKTIVITAS KARYAWAN EARLY CAREER DI KALANGAN GENERASI Z - Firdiani, Cheryl Avril; Olivia, Evera; Reza Fahlevi (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
Generation Z, born between 1995-2012, has a high need for flexibility and balance between work and personal life. The resulting imbalance can cause stress and decreased productivity for employees. This research aims to analyze the role of work-life balance and productivity of Generation Z employees at the early career stage. The method used was quantitative with convenience sampling, involving 164 respondents aged 18-25 years with work experience of less than five years. The research results show that the majority of respondents have low work-life balance and moderate productivity. Linear regression analysis revealed that productivity had a positive and significant effect on work-life balance with an R Square value of 28% and a sig value (p <.001). These findings emphasize the importance of productivity in supporting work and personal life balance for Generation Z in the world of work.